Serial minicuttings technique as a rejuvenation method for Eucalyptus clones - Wendling, Ivar; Xavier, Aloisio (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the efficiency of serial minicuttings technique in four clones of Eucalyptus grandis, regarding to survival, rooting and growth in height and diameter of the seedlings. Seven subcultures, by serial minicuttings technique, through successive rooting of the sprouts were accomplished. Rooting was carried out in a greenhouse during 25 days, followed by ten days acclimatization at shadow house, and final evaluation of the seedlings at 50 days, in the sun. The serial minicuttings technique showed positive effect, mostly for difficult rooting clones.
Keywords: rooting; cloning; forestry; vegetative propagation